2017
DOI: 10.1063/1.4996866
|View full text |Cite
|
Sign up to set email alerts
|

Noise refocusing in a five-blade neutron interferometer

Abstract: We provide a quantum information description of a proposed five-blade neutron interferometer geometry and show that it is robust against low frequency mechanical vibrations and dephasing due to the dynamical phase. The extent to which the dynamical phase affects the contrast in a neutron interferometer is experimentally shown. In our model, we consider the coherent evolution of a neutron wavepacket in an interferometer crystal blade and simulate the effect of mechanical vibrations and momentum spread of the ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…That is, the blades are not positioned at equal distances in this geometry. The cost of breaking this symmetry has been shown recently to cause a decrease in the contrast of the four-blade NI [16]. Stated in another way, the phases occurring due to diffraction inside the blade are not equal for Path I and Path II in this NI geometry.…”
Section: Effects Of Defocussingmentioning
confidence: 96%
See 1 more Smart Citation
“…That is, the blades are not positioned at equal distances in this geometry. The cost of breaking this symmetry has been shown recently to cause a decrease in the contrast of the four-blade NI [16]. Stated in another way, the phases occurring due to diffraction inside the blade are not equal for Path I and Path II in this NI geometry.…”
Section: Effects Of Defocussingmentioning
confidence: 96%
“…In spite of this, the observed contrast of 25% in [14] was less than half of the expected contrast. A recent study suggests that the maximum achievable contrast for the DFS NI is unavoidably less than one [16].…”
Section: Introductionmentioning
confidence: 99%
“…The phase ξ on the diagonals is not physical and thus set to zero. The off-diagonal phase ζ associated with a global lattice translation is important to interferometer simulations [26], where a relative translation of one of the diffracting optics shifts the phase of the measured interference pattern, but it is of no consequence to the simulations presented here and also set to zero.…”
Section: B Quantum Information (Qi) Modelmentioning
confidence: 99%
“…Nsofini et al [25][26][27] demonstrated that many of the results of dynamical diffraction can be reproduced in the Laue case using a quantum information (QI) model, in which neutrons travel through a quantum Galton board where every peg corresponds to the application of a unitary operator on the neutron state. The intensity profiles predicted by the standard results of dynamical diffraction were reproduced with accuracy depending on the amount of layers used to model the crystal thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The recently introduced quantum information (QI) model of DD attempts to simplify the mathematics by treating the neutron propagation as a quantum random walk [24][25][26][27]. Good agreement has been found between the model and the standard DD effects such as the Borrmann triangle, pendellösung oscillations, and the spatial intensity profiles of the NI paths.…”
Section: Introductionmentioning
confidence: 99%